Electrodeposition of Polymer Electrolyte Into Porous LiNi0.5Mn1.5O4 for High Performance All-Solid-State Microbatteries - Salian, Girish D.; Lebouin, Chrystelle; Galeyeva, Alina; Kurbatov, Andrey P.; Djenizian, Thierry (Frontiers in Chemistry, 2019)
We report the electrodeposition of polymer electrolyte (PMMA-PEG) in porous lithium nickel manganese oxide (LiNi0.5Mn1.5O4) cathode layer by cyclic voltammetry. The cathode-electrolyte interface of the polymer-coated LNMO electrode has been characterized by scanning electron microscopy and electrochemical techniques. Electrochemical measurements consisting of galvanostatic cycling tests and electrochemical impedance spectroscopy revealed a significant improvement of the capacity values and the increase of the operating voltage. These effects are attributed to the total filling of pores by the electrodeposited polymer that contributes to improve the reversible insertion of Li+. A complete all-solid-state microbattery consisting of electropolymerized LNMO as the cathode, a thin polymer layer as the electrolyte and TiO2 nanotubes as the anode has been successfully fabricated and tested.